Sexual and reproductive health : a public health perspective - Look, Paul F. A. van; Heggenhougen, Kris (Kristian); Quah, Stella R. (San Diego : Academic Press, 2011)
'This volume presents the highlights of current global thinking about sexual and reproductive health. Major changes have taken place in the last 15 years in the way decision-makers think about the subject and the manner in which programmes deliver comprehensive sexual and reproductive health services. The turning point was the International Conference on Population and Development (ICPD) held in Cairo, Egypt, in 1994. ICPD was a watershed for several reasons. First, more than in any of the preceding United Nations population conferences, the issue of population was clearly placed as being central to sustainable development. Second, the narrow focus on population growth ('the population bomb') which had been a neo-Malthusian concern and preoccupation ever since the Club of Rome published its 1972 report Limits to Growth, was replaced by the comprehensive concept of (sexual and) reproductive health. Third, and linked to the definition and introduction of the reproductive health concept, was the strong call for a paradigm shift away from a policy environment driven by demographic considerations (sometimes to the point of using coercion in family planning services in order to reach demographic targets) to an environment that recognized the right of individuals to make their own choices. And, last but not least, ICPD as well as the Fourth World Conference on Women (FWCW) held the following year in Beijing, People's Republic of China, strongly emphasized that the rights of women and men to good sexual and reproductive health are firmly grounded in universal human rights'--Provided by publisher
Machine generated contents note: Section 1: Physiology, General Epidemiology and Demography Section 2: Core Elements Section 3: Reproductive CancersSection 4: Ethics and other General Aspects.
Keywords: Family Planning Services; Perinatal care; Pregnancy Complications -- prevention & control; Sexually Transmitted Diseases -- prevention & control